Treinamento resistido de intensidade moderada preserva a função vascular mediada por insulina na artéria mesentérica de ratos tratados com dexametasona - Araújo, João Eliakim dos Santos (2020)
Introduction: Glucocorticoids (GC) are used as antiallergic and anti-inflammatory drugs, but their excessive use causes metabolic disorders, resulting in the appearance of metabolic syndrome (MS) and, therefore, endothelial dysfunction. Thus, resistance exercise has been an important alternative in the prevention and treatment of these metabolic disorders that lead to damage to the endothelium, preventing the development of cardiovascular diseases. Objective: To evaluate the capacity of resistance training (RT) to prevent metabolic and vascular changes induced by GC. Methods: Wistar rats were divided into groups: Control (CO), Dexamethasone (DEX) and Dexamethasone + RT (DEX+RT) and weighed weekly. Animals CO, DEX and DEX+RT were adapted (5 days/5 min/day) in the squat device. After adaptation, the groups were submitted to the test of a maximum repetition (1RM), repeated every 2 weeks to maintain the desired intensity. The DEX+RT group was submitted to an RT protocol in 3 series of 10 repetitions, 3 times/week for 8 weeks and with an intensity of 60% of the maximum load established in the 1RM test. The CO and DEX groups were submitted to a fictitious exercise. In the eighth week of resistance training, dexamethasone (DEXA, 2.0 mg/kg, via i.p) was administered for 7 days in the DEX and DEX+RT and 0.9% NaCl groups in the CO group. 48 hours after 1RM, animals were fasted for 8 hours and glucose, insulin, total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL-c) and high density lipoprotein (HDL- c) have been verified. After that, the animals were anesthetized and sacrificed, the superior mesenteric artery was removed and sectioned into rings, and mounted in vats for an isolated organ. Endothelium-dependent vasodilation was achieved through concentration-response curves for insulin, in rings pre-contracted with phenylephrine (Phe). Then, concentration-response curves were obtained for the CO, DEX and DEX+RT groups, in the absence and in the presence of PI3K, NOS, ETA receptor inhibitors, and the vasoconstriction induced by FEN in the absence and presence was also evaluated. of L-NAME. Results: glucose, insulin, CT, TG, LDL-c were increased and HDL-c reduced in the DEX group, but these changes were prevented in the DEX+RT group. Insulin-induced vasodilation was reduced in the DEX group compared to the CO group, however, DEX+TR increased vasodilation in relation to the DEX group. When we evaluated the participation of PI3K after incubation with LY294002, there was a reduction in relaxation in the CO group, while in the DEX group, vasodilation was abolished, showing a similarly contractile effect in the presence of NOS inhibitor, being inhibited with BQ123. However, the contractile effect was abolished in the DEX+RT group. The vasoconstrictor response induced by Phe, increased in the DEX group compared to CO, being reduced in the DEX+RT group. Additionally, after incubation with L-NAME, the vasoconstrictor response was high in all groups, being lower in the CO and DEX+RT group than in the DEX group. Conclusion: RT in the presence of high doses of glucocorticoids, prevented damage to the PI3K/eNOS vasodilator pathway, in addition to attenuating the MAPK/ET-1 vasoconstrictor pathway.